Socioeconomic conditions in childhood, adolescence, and adulthood and the risk of ischemic stroke - Becher, Heiko; Palm, Frederick; Aigner, Annette; Safer, Anton; Urbanek, Christian; Buggle, Florian; Grond-Ginsbach, Caspar; Grau, Armin J. (Stroke, 2016)
Background and Purpose—The association between socioeconomic status in adulthood and the risk of stroke is well established; however, the independent effects of socioeconomic conditions in different life phases are less understood.Methods—Within a population-based stroke registry, we performed a case-control study with 470 ischemic stroke patients (cases) aged 18 to 80 years and 809 age- and sex-matched stroke-free controls, randomly selected from the population (study period October 2007 to April 2012). We assessed socioeconomic conditions in childhood, adolescence, and adulthood, and developed a socioeconomic risk score for each life period.Results—Socioeconomic conditions were less favorable in cases regarding paternal profession, living conditions and estimated family income in childhood, school degree, and vocational training in adolescence, last profession, marital status and periods of unemployment in adulthood. Using tertiles of score values, low socioeconomic conditions during childhood (odds ratio 1.77; 95% confidence interval 1.20-2.60) and adulthood (odds ratio 1.74; 95% confidence interval 1.16-2.60) but not significantly during adolescence (odds ratio 1.64; 95% confidence interval 0.97-2.78) were associated with stroke risk after adjustment for risk factors and other life stages. Medical risk factors attenuated the effect of childhood conditions, and lifestyle factors reduced the effect of socioeconomic conditions in adolescence and adulthood. Unfavorable childhood socioeconomic conditions were particularly associated with large artery atherosclerotic stroke in adulthood (odds ratio 2.13; 95% confidence interval 1.24-3.67).Conclusions—This study supports the hypothesis that unfavorable childhood socioeconomic conditions are related to ischemic stroke risk, independent of established risk factors and socioeconomic status in adulthood, and fosters the idea that stroke prevention needs to begin early in life.